Influência do revestimento de argamassa no transporte de cloretos em estruturas de concreto armado inseridas no meio urbano - Malheiro, Raphaele de Lira Meireles de Castro (2008)
Taking into account the research carried out in João Pessoa City, Paraíba State, Brazil, a significant number of concrete structures in urban environments and subjected to marine influence are covered by mortar. This way, it was studied the relationship between chloride transport in mortar covering and its influence on protection of covered structures. Prismatic concrete specimens were cast with 8x8x8cm and water to cement ratio of 0,55. A thin spatterdash layer was applied in these specimens and, after the curing period, a mortar covering layer done using four different mixtures and two thicknesses. Reference concrete specimens were also cast. After 28 days f curing in laboratory environment, the specimens were painted with epoxy resin in five of their six faces, with the purpose to simulate unidirectional chloride flux. Afterwards, the specimens were put under natural diffusion and wetting and drying cycles in sodium chloride solutions (1M) for 49 days. At the end of this period, chloride profiles were obtained with powered samples extracted each five millimetres from surface to bulk specimen. Results show that there is a chloride accumulation in the interface between mortar and concrete, followed by a chloride content decrease in concrete. This effect is called resistance effect . The mixture and the thickness of covering mortars significantly influence chloride transport in concrete. In a general way, covering mortars can play a complementary protection role in concrete structures. However, as these results were taken under accelerated conditions, they may be taken with caution.